To disclose or not to disclose: Transparency and liquidity in the structured product market - Nils Friewald; Rainer Jankowitsch; Marti G. Subrahmanyam (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We use a unique data set from the Trade Reporting and Compliance Engine (TRACE) to study liquidity e ffects in the US structured product market. Our main contribution is the analysis of the relation between the accuracy in measuring liquidity and the potential degree of disclosure. Having access to all relevant trading information, we provide evidence that transaction cost measures that use dealer specific information such as trader identity and trade direction can be efficiently proxied by measures that use less detailed information. This finding is important for all market participants in the context of OTC markets, as it fosters our understanding of the information contained in transaction data. Thus, our results provide guidance for improving transparency while maintaining trader confidentiality. In addition, we analyze liquidity in the structured product market in general and show that securities that are mainly institutionally traded, guaranteed by a federal authority, or have low credit risk, tend to be more liquid.
Keywords: G12; G14; 330; liquidity; structured products; OTC markets; transparency; TRACE